Synthesis of Ni-Zn And Ni-Zn-Cu Ferrite Via Sol-Gel Route and Solid State Reaction - Zahi, Souilah (2000)
A ferrite is an important class of magnetic materials. At present the major material types for application of spinel soft ferrite are nickel-zinc and manganesezinc ferrites. A majority of these ferrites are synthesised by the classical method which is the conventi onal ceramic process known as sol id state reaction (SSR). Most nonconventional processes for powder preparation are wet methods. Some of these processes are co-precipitation; organic precursors; co-spray roasting; freeze drying; sol-gel route (SGR). prepared by two different processes: the first i s solid state reaction and the other is sol-gel route. Different starting materials are used and the process of sol-gel technique is well known. The synthesis of these compounds via sol-gel technique is carried out. Scanning electron microscope, Infrared spectroscopy and X-ray analyses of various gel samples with different thermal history helped in identifying the reaction process and the stages where amorphous-gel-to-crystalline phase transition occurred.The utilization of sol-gel technique is successful. Comparison of the results for samples demonstrates that the microstructural, magnetic and electrical properties of soft ferrites are improved, and some interesting advantages are realized such as low temperature of preparation, better homogeneity and well-defined polycrystalline microstructure. In addition, a new important advantage has been found in this research, which is short processing time of gel preparation.